The NEET youth: European context and Russian realities - M. B. Bulanova (RUDN journal of Sociology, 2020)
The article attempts to identify features and provide a social portrait of the NEET youth in the European and Russian contexts. The developed European countries faced the NEET phenomenon in the late 20th - early 21st century: according to the Eurostat definition, this group includes young people aged 15-24, unemployed or economically inactive, who do not study and do not get vocational training - in 2017, the NEET youth made on average 14.7% of the working population. In Russia, the number of NEETs is at the average European level - 15%. According to the classification of the International Labor Organization (ILO), there are two groups of NEETs: NEET-unemployed and NEET-inactive. The authors consider as the determining factor of becoming a part of the NEET group one’s unwillingness to work and study, i.e. the criteria of being NEET is not working (rather than being unemployed) and not studying (rather than being economically inactive). Thus, it is the forms of ‘social dependency’ of the NEET youth that make the study of this group so difficult. The article examines objective and subjective reasons for the emergence of this group and social consequences of being in the NEET group, whose representatives try to benefit from the situation. The authors show that the assessment of the NEET youth as marginal, i.e. a transitional and unstable group, encourages European states to provide assistance to these young people to help them to get out of the situation of non-working and non-studying. The article provides some examples of such assistance in Italy, Great Britain, Poland, Spain, and the Netherlands.